WHEN WATER IS SCARCE, WE SUFFER TOO: Water Scarcity through the Eyes of Children in an Urban Poor Community - Barrameda, Teresita Villamor (Philippine Journal of Social Development, 2011)
The article describes the effects of water scarcity on households in an urban poor setting, as seen through the eyes of children. Using the conceptual frame of deprivation and viewing access to water as a basic human right, it examines water deprivation as one of the indicators of poverty. Through a case study, the paper shows how water scarcity adversely affects children who are among the most vulnerable members of poor households.